Mechanism of calcium hydroxide-induced neutrophil migration into air-pouch cavity - Teixeira de Moraes Costa, Mariana Machado [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Gomes-Filho, Joao Eduardo [UNESP] (Mosby-elsevier, 2008)
The aim of this study was to investigate cellular migration induced by calcium hydroxide to air-pouch cavities in mice. The migration was more specific to neutrophil and was dose and time dependent (peaking 96 h after stimulation). This migration was inhibited by pretreatment with thalidomide, indomethacin, MK886, meloxicam, dexamethasone, MK886 associated with indomethacin, and MK886 associated with indomethacin and dexamethasone. The air-pouch exudate from animals stimulated with calcium hydroxide showed an increase of leukotriene-B4 (LTB4), interleukin-1 beta, tumor necrosis factor alpha (TNF-alpha), cytokine-induced neutrophil chemoattractant (KC), and macrophage inflammatory protein 2 (MIP-2) release. Pretreatment with 3% thioglycollate increased the macrophage population in the air pouch but did not change neutrophil migration. Depleting the resident mast cells through chronic pretreatment with compound 48/80 did not alter neutrophil migration in response to calcium hydroxide. It was possible to conclude that calcium hydroxide-induced neutrophil migration to the air-pouch cavity in mice is mediated by LTB4, TNF-alpha, KC, MIP-2, and prostaglandins, but it was not dependent on macrophages or mast cells.